Mapping of National Climate Change Policies and Stakeholders in Cambodia, Philippines, Thailand, and Viet Nam - Mirzabaev, Alisher; Gonzalez, Tobiah; Pajadan, Karen; Dohrmann, Christian; Sander, Bjoern Ole (International Rice Research Institute, 2025)
This report is a compilation of the national policies, GHG emission reduction targets, identification of key stakeholders and of their roles, and decision-making structures governing climate change mitigation under the Nationally Determined Contributions (NDCs) in Cambodia, the Philippines, Thailand, and Viet Nam.